Representaciones del crimen y el homicidio en Medellín - Colombia (1910 – 1930) (2016)
ABSTRACT: In this article it will first be contrasted the alarming tone of press reports and official statements that refer to the alleged growth of criminality in Medellin, at the beginning of the 20th century, with some statistical data that disproved them. A reference will then be made to one of the manifestations of urban violence that usually led to grave injuries or homicides: the quarrel. Finally, a recognition will be made of the places frequently associated with homicides; spaces that were associated to crime, and at which the vigilance and control by authorities was progressively demanded.